Desenvolvimento e validação de metodologia analítica por cromatografia líquida de alta eficiência da Cannabis spp. - Segundo, Carlos Espínola Neto (2023)
With the increase in the scientific evidence on the therapeutic properties of Cannabis, the demand for medicines containing its active ingredients has also increased. Due to the bureaucracy and legislation still under construction in Brazil and worldwide, many families seek this treatment through unregistered medicines where many do not meet the standards of good manufacturing practices, putting the patient's health at risk. In this context, it is important to develop quality control techniques aimed at reducing the risks for the population requiring this treatment. Cannabis spp. has in its composition over 565 substances and because of its therapeutic relevance, it is necessary to develop efficient analytical methods to separate and subsequently identify and quantify the compounds present in it. Hence, this work aimed to develop a high-performance liquid chromatography (HPLC) analytical method for 3 of the main phytocannabinoid markers of Cannabis spp. as well as to validate it according to what is regulated by ANVISA through RDC 166/2017 and thus be used in the quality control of these medicines. Reference chromatographic standards of Δ⁹-tetrahydrocannabinol (Δ⁹THC), Cannabidiol (CBD), and Cannabinol (CBN), and the oils provided by the Associação Brasileira de Apoio Cannabis Esperança, which are oily solutions of Cannabis spp. extracts rich in Δ⁹-THC and CBD, standardized as follows: CBD oil 20mg/mL (classic and gold) Δ⁹-THC oil 15mg/mL (classic and gold) and Δ⁹-THC:CBD oil 15mg/mL (classic and gold), were used for the method development and validation. CBN is an important marker for the stability of cannabis products because it is the degradation product of Δ⁹-THC. After all parameters were evaluated, it was concluded that the methodology for the quantification of cannabinoids CBD, CBN and Δ⁹ -Δ⁹-THC in the oil products was validated according to RDC 166/2017. The method can be used to quantify cannabinoids in oils with adequate precision and accuracy at a concentration of 1.5 µg/mL and above.